2009
DOI: 10.1128/iai.01571-08
|View full text |Cite
|
Sign up to set email alerts
|

Children with the Le(a+b−) Blood Group Have Increased Susceptibility to Diarrhea Caused by Enterotoxigenic Escherichia coli Expressing Colonization Factor I Group Fimbriae

Abstract: Recent studies have shown that children with blood group A have increased susceptibility to enterotoxigenic Escherichia coli (ETEC) diarrhea and that Lewis blood group "a" antigen (Le a ) may be a candidate receptor for ETEC colonization factor (CF) antigen I (CFA/I) fimbriae. Based on these findings, we have attempted to determine if children with the Le(a؉b؊) phenotype may be more susceptible to diarrhea caused by ETEC, in particular ETEC expressing CFA/I and related fimbriae of the CFA/I group, than Le(a؊b؉… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 25 publications
5
38
1
Order By: Relevance
“…However, it is notable that major rotavirus strain variations in HBGA recognition were detected. The relevant human clinical strain Wa did not recognize HBGAs, which is consistent with the observed lack of influence of genetically controlled expression of different HBGAs on pediatric rotavirus gastroenteritis 46,47 . Interestingly, two recent studies suggested that non-secretor individuals (null homozygote fucosyltransferase, FUT2) are not susceptible to infection with the most common rotaviruses 48,49 .…”
Section: Discussionsupporting
confidence: 81%
“…However, it is notable that major rotavirus strain variations in HBGA recognition were detected. The relevant human clinical strain Wa did not recognize HBGAs, which is consistent with the observed lack of influence of genetically controlled expression of different HBGAs on pediatric rotavirus gastroenteritis 46,47 . Interestingly, two recent studies suggested that non-secretor individuals (null homozygote fucosyltransferase, FUT2) are not susceptible to infection with the most common rotaviruses 48,49 .…”
Section: Discussionsupporting
confidence: 81%
“…A study in Bangladesh, following ETEC diarrhea of children during their first 2 years of life, noted that ST-expressing ETEC more frequently infected children with blood type A or AB than children with blood group O (698). Further studies determined that children with Lewis antigen Le(aϩbϪ), but not Le(aϪbϩ), were more susceptible to illness caused by ETEC that expresses the CFA/I group of CFs (706). This association was suggested to be because of the ability of CFA/I to adhere to Le a -terminated glycosphingolipids but not Le b -terminated glycosphingolipids on host cells (706,707).…”
Section: Epidemiologymentioning
confidence: 99%
“…RVs of P [1], P [2], P [3], and P [7] genotypes can be found in both humans and animals, and these RVs are mainly sialidase sensitive (9). Three P types (P [4], P [6], and P [8]) have been found to commonly cause gastroenteritis in humans, but none of them are sialidase sensitive (8).…”
mentioning
confidence: 99%